Review of final-year medical students’ rural attachment at district hospitals in KwaZulu-Natal: student perspectives - P. Diab; P.D. McNeill; A.J. Ross (South African Family Practice)
Objectives: This study aimed to investigate the views of students involved in rural community-based medical attachments during their final year at medical school. The programme has been in existence for some time, but no formal evaluation thereof has yet taken place. This paper describes the first two phases of what is described as a quality improvement project: namely to describe the problem state and to discuss possible activities to improve the programme.